Tipologías Textuales en el desarrollo del Pensamiento Crítico, en los niños y niñas del 4to año de Educación General Básica de la Unidad Educativa Amelia Gallegos Díaz, de la Ciudad de Riobamba, Provincia de Chimborazo, periodo 2015-2016 - Guamán Pulig, Vilma Esperanza (2016)
This research was conducted in the 4th year of “Amelia Díaz Gallegos”. General Education Basic Unit. In which it took into account different types of methodologies and teaching strategies thus realizing a significant learning, therefore we gave to know the characteristics, strategies, types and classification of text types to develop critical thinking in this institution, because it is a cognitive process of rational, thoughtful and analytical character whose purpose, reasoning efficiently, make value judgments, decision making and problem solving, for this exploratory research was used through this we learned more about the subject, and once diagnosed research also aims to identify and resolve fundamental problems, find answers to unknown questions about the topic. In the implementation of this project participated children of the educational institution in the company of the teacher, justifying its marking both the importance and the interest in the development of critical thinking textual typologies comprising, as a primary tool in daily life contributing to reflection. The technique used was the survey and the instrument the questionnaire which provided us gather information, verifying which were its shortcomings by the results that approached this study, in this way a solution to the problem occurred expanding knowledge of learners, since learners require in each year appropriate texts according to their ages and environment where they develop it is important to work in their previous knowledge to new, therefore the teacher should be a guide, counselor and friends of this student. All our information used is attached in the references that are attached in the investigation